2017
DOI: 10.18203/2349-2902.isj20175892
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of sublay versus onlay meshplasty in incisional and ventral hernias

Abstract: Background: Hernia derived from the Latin word, is a protrusion of a viscus or part of a viscus through an abnormal opening in the walls of its containing cavity. Objectives of present study were to evaluate sublay Vs onlay meshplasty in incisional and ventral hernia and to compare and determine duration of operation and hospital stay, post-operative complications and recurrences.Methods: The study was conducted at Dr. D. Y. Patil Medical College and Hospital, DPU University, for a period of 2 years (from July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 12 publications
11
8
0
Order By: Relevance
“…27 On comparison of average duration of surgery our study was concordant to study by Baracs and Dhaigude who also showed shorter duration of surgery in anatomical repair compared to mesh repair and among mesh repair surgery by sublay technique was longer than onlay technique which could be explained with easier operative onlay technique. 17,28 Based on distribution of postoperative complications between anatomical and mesh repair groups our study is similar to the study by Luijendijk and Shiv Kumar but differs from study by Jehad who showed increased incidence of seroma formation in anatomical repair group. 11,16,21 Superficial wound infection was the second most common complication observed in our study.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…27 On comparison of average duration of surgery our study was concordant to study by Baracs and Dhaigude who also showed shorter duration of surgery in anatomical repair compared to mesh repair and among mesh repair surgery by sublay technique was longer than onlay technique which could be explained with easier operative onlay technique. 17,28 Based on distribution of postoperative complications between anatomical and mesh repair groups our study is similar to the study by Luijendijk and Shiv Kumar but differs from study by Jehad who showed increased incidence of seroma formation in anatomical repair group. 11,16,21 Superficial wound infection was the second most common complication observed in our study.…”
Section: Discussionsupporting
confidence: 82%
“…On comparing seroma formation in onlay and sublay group our study was concordant with the study of authors Baracs, Lamani and Dhaigude who also observed increased incidence of seroma formation in onlay group. 17,28,29 In our study incidence of wound infection was 15% in onlay group while in sublay group it was 10% similar to the study by authors. 17,28,29 In terms of recurrence rate our study is comparable to the study by Luijendijk, Baracs, Kumar, Tulaskar and Jacobus who also found increased incidence recurrence in anatomical repair group compared to mesh repair.…”
Section: Recurrencessupporting
confidence: 90%
See 3 more Smart Citations